The Effect of Ability and Motivation on Organizational Citizenship Behavior - Rachmawaty, Arvita (KINERJA, 2024)
The purpose of this study is to analyze the direct influence of Ability and Motivation on OCB and police personnel performance. In addition, it is also to analyze the indirect influence of Ability and Morphation through OCB on the performance of police personnel. The respondents studied were 70 police personnel who worked in the Samarinda Police Criminal Investigation Unit. The analysis model used in this study is Path analysis. The results of the study concluded that Ability had a significant positive effect on OCB. Motivation had a positive but not significant effect on OCB. The direct influence of Ability and Motivation as well as OCB is positive and significant on Performance. But indirectly, Capability and Motivation through OCB have a not significant effect on the performance of personnel of the Samarinda Police Criminal Investigation Unit.